Redesain Tata Letak Fasilitas Produksi IKM Virgin Coconut Oil di Kota Pariaman - Syamsul Anwar; Rizki Alfi; Verra Syahmer; Nadya Rishelin; Kushisa Atta Jaeba; Tosty Maylangi Sitorus; Adlina Safitri Helmi; Erwinsyah Sipahutar (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2026)
The production facility layout plays a vital role in enhancing the operational performance of Small and Medium Enterprises (SMEs). An SME in the Virgin Coconut Oil sector currently faces efficiency constraints due to an unorganized production flow. This Community Service Program (PKM) aims to redesign the SME's production facility layout to make it more effective, efficient, and compliant with sanitation standards. The implementation method consisted of three integrated stages: (1) field observation and problem identification, (2) designing a proposed layout using From-To Chart, Activity Relationship Chart and Activity Relationship Diagram instruments, and (3) socialization, design handover, and program evaluation. The result of this program is a new layout design featuring a U-shaped flow that minimizes material movement time while integrating ergonomic principles and work environment sanitation. Evaluation and feedback from the partner indicated a high level of acceptance, as the design successfully addressed the SME's operational needs. This redesigned layout is expected to serve as a strategic reference for related SMEs in optimizing production space and improving productivity sustainable.